Body awareness and chronic low back pain: validity and reliability study of Turkish version of body awareness rating scale - DEMİREL, Aynur (Turk J Med Sci, 2020)
BACKGROUND/AIM: Previous studies reported that patients with chronic low back pain (CLBP) had trouble describing senses or body functions. A questionnaire, the body awareness rating questionnaire (BARQ), was recently developed for assessing body awareness. The aim of the study was to develop a Turkish version of the BARQ and investigate the validity and reliability in patients with CLBP. MATERIALS AND METHODS: BARQ translated to Turkish with forward-backward method. Ninety-nine patients with CLBP and 101 healthy controls (HC) completed the BARQ-T. Fifty-one of patients with CLBP and HC repeated BARQ-T 3 days later. In addition to BARQ-T, Oswestry disability index (ODI), pain severity, short form 36 (SF-36) and Toronto alexithymia scale (TAS) were administered. RESULTS: The current study found good-excellent Cronbach’s alpha values for patients with CLBP (α: between 0.883–0.967) and acceptable-good Cronbach’s alpha values for HC (α: between 0.649–0.825) in factors of BARQ-T. ICC values for test-retest validity were found to be good-excellent for patients with CLBP in all factors. BARQ-T was positively correlated with SF-36 and negatively correlated with ODI and TAS (P < 0.05). CONCLUSION: The study confirmed that the BARQ-T has acceptable validation and reliability in terms of pain perception and pain assessment in the Turkish CLBP community.